Fixation Improvement through Biofeedback Rehabilitation in Stargardt Disease - G. Scuderi; F. Verboschi; D. Domanico; L. Spadea (Case Reports in Medicine)
Stargardt disease is the most common hereditary macular degeneration in juveniles. It is characterized by macular dystrophy associated with loss of central vision in the first or second decade of life, a “beaten-metal” appearance in the fovea or parafoveal region, yellowish flecks around the macula or in posterior area of the retina, progressive atrophy of the bilateral foveal retinal pigment epithelium, and the “dark choroid” sign on fundus fluorescein angiography in most cases. We report a case of Stargardt disease in a 26-year-old Caucasian female submitted to rehabilitative training with microperimetry MP-1 to find a new preferred retinal locus (PRL) and to train her to better her quality of life. Best corrected visual acuity, mean retinal sensitivity, fixation, bivariate contour ellipse area, and speed reading were evaluated before and after the training and results were discussed.